Le Chat Botté - Charles Perrault (World's Work, 1977)
A miller had three sons, and when he died he left them nothing but his mill, his donkey, and his cat.
Droits : Métadonnées bibliographiques issues d Open Library
Keywords: open library; histoire; Géographie; livre; Nursery rhymes; france; Children's stories; French; Fairy tales; Histoire